(untitled) (ModaPalavra e-periódico, 2025)
The overall objective of this research is to develop an initial framework regarding the study of color trends that incorporates consumer behavior studies. Thus, to achieve the proposed objectives, this research was guided by bibliographical and documentary research, and empirical research. For the empirical research, the methodology used was grounded theory. The data collection technique was through interviews with market professionals working in the function of determining color trends. Business reports on color trends were also analyzed, with studies of the Zeitgeist, coolhunting and proposed color palettes. From these data collected in the empirical research, together with secondary data from bibliographical research, general guidelines were drawn for the development of a theoretical scheme of color trends that incorporates studies of consumer behavior.